Reflections on agrarian, regional and comparative history: land leases for cereal agriculture in the late colonial period (Quinto Sol, 2013)
The development of research in Regional History in Argentina allows us to wonder about the directions that are being defined. Once a phase of accumulation of information and well-founded descriptions has been completed, it is necessary to advance in explanations that can account for a whole range of common phenomena. In this sense, the challenge is to face generalization without losing the “flavor” of the inalienable specificities for historical knowledge.
Keywords: agrarian history; rural lease; late colonial period; comparisons